Environmentally Friendly Agro-Industry Business Model as an Effort to Increase the Competitiveness of Local Agricultural Products - Mazloum Yar, Fayaz; Akpoviroro, Kowo Solomon; Abozi, Ezinne (Politeknik Siber Cerdika Internasional, 2024)
The environmentally friendly agro-industry business model is an important strategy in increasing the competitiveness of local agricultural products in the global market. The background of this study is the increasing consumer awareness of sustainable products, while local agro-industry players in Indonesia still face challenges in adopting environmentally friendly business models. This study aims to identify factors that influence the adoption of environmentally friendly business models and evaluate their impact on production efficiency and product competitiveness. Using qualitative and quantitative descriptive methods, this study involved a survey of 50 agro-industry players and in-depth interviews to obtain quantitative and qualitative data. The results showed that the implementation of environmentally friendly business models contributed to increased energy efficiency, reduced operational costs, and increased consumer loyalty. Although there are constraints on costs and access to technology, the long-term benefits of this business model promise stronger competitiveness in the international market. This study is expected to be a guide for policy makers and business players in developing sustainable and competitive agro-industry.